„Wild Fields” – a borderland between a nomadic and settled lifestyle in the north-western part of the Black Sea basin - Czamańska, Ilona (Balcanica Posnaniensia. Acta et studia, 2007)
From ancient times until the 18th century, the areas located in the north-western part of the Black Sea basin constituted a characteristic borderland between nomadic and sedentary lifestyles. These were places where different forms of social, economic and political organisation clashed. Their common features included ambiguous national affiliation, low population density and an ethnic and cultural mosaic. The aim of this article is to show the civilisational specificity of these territories, their role in contacts between nomadic and sedentary communities, and to trace the mechanisms of social transformation. The author draws on a wide range of sources – Byzantine, Hungarian, Ruthenian and Turkish chronicles – as well as historical studies on migration and colonisation. By comparing examples from different regions, she identifies common features and differences in development processes. She formulates the following conclusions: firstly, the borders of the borderland zone underwent relatively minor shifts over a long period of history, despite changing political and military factors; secondly, the coexistence of nomadic and settled populations fostered the emergence of mixed economies and the gradual assimilation of nomads; thirdly, weak control by central authorities led to the development of informal military structures, often modelled on the organisation of nomads.